ANALISIS PERTUMBUHAN KEDELAI VARIETAS GROBOGAN PADA CEKAMAN KEKERINGAN - Achmad Fatchul Aziez; Teguh Supriyadi; Tyas Soemarah Kurnia Dewi; Angga Firman Saputra (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2021)
Soybean (Glycine max (L.) Merril) is one of the main food commodities in Indonesia. Soybean production has not been able to meet domestic food needs, one of the causes is the existence of drought stress. The aim of this study was to analyze the growth of soybean plants at different levels of drought stress at various stages of growth. This research was conducted in a plastic house in Demangan village, Sambi district, Boyolali district from August to December 2020. The study used a completely randomized design with 2 factors and 3 replications. The first factor is soil moisture content ei. 100%, 75%, 50% 25% of field capacity. The second factor is the time of drought stress which includes the active vegetative phase, the flowering phase, and the seed filling phase. The parameters observed were Leaf Area Index (LAI), Specific Leaf Area (SLA), Crop Growth Rate (CGR), and Net Assimilation Rate (NAR). The results of this study indicated that drought stress in the pod filling phase reduced LAI, SLA, NAR, and CGR.